SISTEM PROTEKSI OVER CURRENT RELAY MOTOR FORCED DRAFT FAN PADA PEMBANGKIT LISTRIK TENAGA UAP - Aulia Vici Yunitasari; Subuh Pramono (Jurnal Teknologi, 2021)
side the power plant uses an electric motor as equipment to convert electrical energy into mechanical, which uses a 3 phase motor. The Steam Power Plant has FDFan which functions as a device that supplies or forces outside air into the boiler combustion chamber. If the power plant operates, there will certainly be many disruptions which will occur due to several factors. Each motor has its own protection system. Especially on the FDfan 3A motor at the PLTU has several protection systems, including Over Current Relay as protection from overcurrent resulting in short circuit current, then Overload Relay as overload protection. In this report, mathematically analyzing calculations and comparing to determine the starting motor current and pick up current in the relay when under normal conditions or in trip conditions. At the power plant unit 3 FDFan motor with a power of 1722 kW produces a starting motor current of 118 A at the test value and the value of the mathematical calculation of 108.86 A. While the overcurrent relay with a pick up value of 4 A and the value of the mathematical calculation of 4.08 A which can be said to be still relatively normal and in good condition. Overcurrent protection relay is needed on the FDFan motor to prevent overcurrent, it is necessary to adjust the current according to the nameplate so that the motor is working optimally.